Korelasi Antara Emotional Maturity dengan Prokrastinasi Akademik pada Mahasiswa - Sari Rahmadani; Ria Okfrima; Vio Reky Vael (Psyche 165 Journal, 2023)
In doing the assignments given by the teacher, there are students who do it right away, but there are also those who delay doing it. His research aims to determine the corellation between emotional maturity and academic procrastination in Mathematics Study Program students at Sjeh M. Djamil Djambek Bukittinggi State Islamic University. The independent variable in this study is emotional maturity and the dependent variable is academic procrastination. The measuring tools used in this study are the emotional maturity scale and the academic procrastination scale. Determining the number of samples in this study using the sampling method is a way to determine the number of samples that meet the following requirements: the number of population is known; at the level of error (significance level) 1%, 5% and 10%; and this method is specifically used for normally distributed samples. Therefore the students used as the research sample were 176 people with a significant level of 10% in the mathematics study program class of 2016 to 2022 at the State Islamic University of Sjech M. Djamil Jambek Bukittinggi. Test the validity and reliability in this study using the Cronbach Alpha technique. The results of the validity coefficient on the emotional maturity scale with a corrected item-total correlation ranged from 0.406 to 0.785 while the reliability coefficient was 0.942. The results of the validity coefficient on the academic procrastination scale with the corrected item-total correlation ranged from 0.306 to 0.781 while the reliability coefficient was 0.952. Based on data analysis, a correlation value of -0.544 with a significance level of 0.000 is obtained, which means the hypothesis is accepted. This shows that there is a negative and significant relationship with the moderate category between emotional maturity and academic procrastination in mathematics study program students at the State Islamic University of Sjeh M. Djamil Djambek Bukittinggi. The effective contribution of the emotional maturity variable to the academic procrastination variable is 30%.